2016
DOI: 10.1371/journal.pone.0152503
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Acute Gastroenteritis Outbreaks Caused by Human Calicivirus (Norovirus and Sapovirus) in Catalonia: A Two Year Prospective Study, 2010-2011

Abstract: BackgroundThe epidemiology of cases of acute gastroenteritis (AGE) of viral etiology is a relevant public health issue. Due to underreporting, the study of outbreaks is an accepted approach to investigate their epidemiology. The objective of this study was to investigate the epidemiological characteristics of AGE outbreaks due to norovirus (NoV) and sapovirus (SV) in Catalonia.Material and MethodsProspective study of AGE outbreaks of possible viral etiology notified during two years in Catalonia. NoV and SV we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
0
15
1
Order By: Relevance
“…NoV and SaV are the most significant viral pathogens associated with food-and water-borne outbreaks of acute gastroenteritis worldwide. 6,11 Wide variety of foods, waters, and environmental sources that is, bivalve shellfish, sandwiches, salads, lettuces, vegetables, tap water, canal water, drinking water, and waste water have been found to be contaminated by NoV and SaV, however, there is very little data on diarrhea associated with NoV and SaV contamination in food supplies and environmental sources in Thailand. In December 2005, NoV contamination was reported in oysters obtained from local markets in Bangkok as well as from oyster farms in southern part of Thailand.…”
Section: Contaminations Of Nov and Sav In Food Supplies And Environmentioning
confidence: 99%
See 1 more Smart Citation
“…NoV and SaV are the most significant viral pathogens associated with food-and water-borne outbreaks of acute gastroenteritis worldwide. 6,11 Wide variety of foods, waters, and environmental sources that is, bivalve shellfish, sandwiches, salads, lettuces, vegetables, tap water, canal water, drinking water, and waste water have been found to be contaminated by NoV and SaV, however, there is very little data on diarrhea associated with NoV and SaV contamination in food supplies and environmental sources in Thailand. In December 2005, NoV contamination was reported in oysters obtained from local markets in Bangkok as well as from oyster farms in southern part of Thailand.…”
Section: Contaminations Of Nov and Sav In Food Supplies And Environmentioning
confidence: 99%
“…They are currently recognized as etiological agents of acute gastroenteritis in humans and animals . In human, both of them cause the disease of all age groups in outbreaks and sporadic cases worldwide . The outbreaks usually occur in semi‐closed settings such as cruise ships, hotels, military facilities, schools, day‐care centers, nursing homes, and hospitals .…”
Section: Introductionmentioning
confidence: 99%
“…Sapovirus (SaV) is one of the important pathogens that cause outbreaks and sporadic cases of acute gastroenteritis (AGE) in people of all ages worldwide (Torner et al, 2016). Prevalences of SaV infection have been reported between 0.2% and 39% in children with AGE (Magwalivha et al, 2018) and between 2.2% and 15.6% in all age groups (Oka et al, 2015;Varela et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There were 203 NoV outbreaks were reported to Shenzhen Center for Disease Control and Prevention. The NoV infection was initially described as "winter vomiting disease" due to its seasonal preference [31], monthly distribution also indicated that the peak of the outbreak in Shenzhen was during the November to March. Previous study have found a link between NoV's increased number and climate or weather [32,33].…”
Section: Hbga-binding Pro Le Epitopes Predicted and Epitope A To E Smentioning
confidence: 99%